Engineering capacitive contribution in nitrogen-doped carbon nanofiber films enabling high performance sodium storage. (April 2018) - Zhu, Hang; Wang, Caiyun; Li, Chengye; Guan, Lingling; Pan, Hongge; Yan, Mi; Jiang, Yinzhu
Abstract: Anode materials have become one of the primary bottlenecks for the development of rechargeable sodium ion batteries. To explore novel carbon-based anodes enabling high performance sodium storage is urgently desirable but remains quite challenging. Herein, we demonstrates excellent sodium storage performance in nitrogen-doped flexible carbon nanofibers as anodes for sodium ion batteries, through engineering capacitive contribution from regulating surface specific area and porosity. Owing to its unique structural feature and uniform nitrogen doping, the derived free-standing carbon nanofibers film achieves a high reversible capacity of 349.1 mAh g −1 at 50 mA g −1 . Even cycled at a high current density of 1 A g −1, the electrode still retains a high capacity of 203.1 mAh g −1 after 1000 extremely stable cycles. The engineering on capacitive contribution in sodium storage might open up possibilities for exploring high performance carbon-based anodes of sodium ion batteries. Graphical abstract: Image 1